Using the G+ tools to validate gender equitable breeding decisions for new cassava varieties targeted at men and women in Nigeria - Nwanze-Olaosebikan, Olamide; Teeken, Béla; Balogun, Ireti; Madu, Tessy; Okoye, Benjamin; Abolore, Bello; Polar, Vivian; Ashby, Jacqueline A.; Cole, Steven M.; Kulakow, Peter A.; Parkes, Elizabeth Y. (International Institute of Tropical Agriculture, 2023)
This study used the G+ tools to investigate: (a) relevant gender and social diversity among cassava users related to granulated and paste food products value chains (VC), and (b) prioritized quality traits (PQTs) that should be incorporated into breeding new cassava to achieve equitable benefits for men and women cassava VC actors in Nigeria. The G+ tools were used to synthesize literature on cassava production, processing and products’ market segments. Furthermore, survey, participatory processing and consumers testing data were triangulated to identify PQTs to fill the G+ product profile templates. Gender impact scores were calculated to categorize PQTs into essential/must-have, niche, added-value and winning traits. The customer profile showed that the VC actors from production to final food product are gendered with high poverty levels among the dominant granulated and paste products VC actors. The gender impact scores per trait validated that high dry matter/ dry matter stability, multiple product-use, high root yield, ease of peeling, stem storability, good food color, texture and swelling are essential/must-have PQTs from a gender perspective across the various stages. For instance, “multiple product-use” enables men and especially women to make choices related to profit, household food needs, and different workload involved for different final products. Applying G+ tools provided a realistic overview of where donors can invest, forecasting equitable benefits and possible harm regarding traits in the product profile, and identified PQTs that breeders are to incorporate to achieve impact on gender equality, nutrition security, increased incomes and resilience among cassava users.